Обґрунтування методики дослідження енергетичних характеристик геліосушарки й метрологічних властивостей засобів вимірювання теплотехнічних параметрів - Коробка, Сергій Васильович; Скляр, Радміла Вікторівна; Стукалець, Ігор Геннадійович; Кригуль, Роман Євгенович; Дудко, Ілля Олександрович; Korobka, Sergiy; Skliar, Radmila; Stukalets, Ihor; Krygul, Roman; Dudko, Illia (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: У роботі представлено розроблення та обґрунтування методики дослідження енергетичних характеристик геліосушарки з урахуванням метрологічних властивостей засобів вимірювання теплотехнічних параметрів. Основна увага приділена визначенню впливу параметрів теплоносія, інтенсивності сонячного випромінювання та ефективності теплообміну на енергетичну продуктивність установки. Проведено аналіз точності вимірювань температури, вологості та швидкості повітря за допомогою термопарних сенсорів, що дало змогу встановити їх метрологічні характеристики та оцінити похибки вимірювань у реальних умовах експлуатації. Запропонована методика дає змогу комплексно оцінювати енергоефективність процесу сушіння, оптимізувати режими роботи геліосушарки та підвищити достовірність експериментальних даних. Отримані результати можуть бути використані для вдосконалення конструкцій сонячних сушильних установок і розроблення систем контролю теплотехнічних параметрів у відновлюваних енергетичних технологіях. /// EN: The study presents the development and justification of a methodology for investigating the energy characteristics of a solar dryer, taking into account the metrological properties of measuring instruments for thermal parameters. The main focus is placed on determining the influence of heat carrier parameters, solar radiation intensity, and heat exchange efficiency on the energy performance of the system. An analysis of measurement accuracy for temperature, humidity, and air velocity was carried out using thermocouple sensors, which made it possible to establish their metrological characteristics and evaluate measurement errors under real operating conditions. The proposed methodology provides a comprehensive evaluation, optimization of the operating modes of the solar dryer, and improvement of the reliability of experimental data. The obtained results can be applied to improve the design of solar drying units and to develop control systems for thermal parameters in renewable energy technologies. The methodology integrates experimental and analytical approaches to assess the dynamics of heat transfer and energy conversion processes within the solar drying chamber. It also provides a basis for evaluating the influence of environmental factors on the efficiency of solar energy utilization. The systematic approach proposed in this work allows for establishing correlations between measured thermal parameters and the overall performance indicators of the system. This ensures not only accurate energy analysis but also supports further research in the development of intelligent monitoring and control systems for solar-powered thermal technologies. The obtained results contribute to improving the accuracy of experimental measurements, the reliability of energy audits, and the practical applicability of solar dryers.
Justification of the methodology for investigating the energy characteristics of a solar dryer and the metrological properties of means for measuring thermal parameters
Keywords: сонячна енергія; геліосушарка; температурно-вологісні поля; тепломасоперенесення; інтенсифікація; конвективне сушіння; solar dryer; temperature-humidity fields; heat and mass transfer; intensification; convective drying.; solar energy